2021
DOI: 10.1111/cdev.13564
|View full text |Cite
|
Sign up to set email alerts
|

Temperamental Shyness, Frontal EEG Theta/Beta Ratio, and Social Anxiety in Children

Abstract: The authors examined how children's frontal electroencephalogram (EEG) theta/beta ratio-an index of neurocognitive control-changed from baseline to a social stressor, and whether these EEG changes moderated the relation between temperament and anxiety. Children (N = 152; M age = 7.82 years, 52% male, 81% White) had their EEG recorded during a baseline and speech anticipation condition. Children's frontal theta/beta ratio decreased from baseline to speech anticipation, and this baseline-to-task change moderated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 63 publications
(126 reference statements)
6
13
0
Order By: Relevance
“…In the unfamiliar condition, we found that shyness was negatively associated with social support seeking at high levels of inhibitory control and unrelated to social support seeking at low levels of inhibitory control. These results are in line with previous studies that have examined the moderating role of a physiological, behavioral, or temperamental index of inhibitory control in the relation between shyness or related constructs and various psychosocial outcomes (Brooker et al, 2016;Henderson, 2010;Lahat et al, 2014;Lamm et al, 2014;Poole et al, 2021;Sette et al, 2018;Thorell et al, 2004;Troller-Renfree et al, 2019;White et al, 2011). Together, these studies converge with our findings to suggest that, at least in an unfamiliar context, higher levels of inhibitory control interfere with more positive and approach-related socioemotional and psychological outcomes, and in this case, observed social support seeking.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In the unfamiliar condition, we found that shyness was negatively associated with social support seeking at high levels of inhibitory control and unrelated to social support seeking at low levels of inhibitory control. These results are in line with previous studies that have examined the moderating role of a physiological, behavioral, or temperamental index of inhibitory control in the relation between shyness or related constructs and various psychosocial outcomes (Brooker et al, 2016;Henderson, 2010;Lahat et al, 2014;Lamm et al, 2014;Poole et al, 2021;Sette et al, 2018;Thorell et al, 2004;Troller-Renfree et al, 2019;White et al, 2011). Together, these studies converge with our findings to suggest that, at least in an unfamiliar context, higher levels of inhibitory control interfere with more positive and approach-related socioemotional and psychological outcomes, and in this case, observed social support seeking.…”
Section: Discussionsupporting
confidence: 93%
“…The present study had several strengths, including the use of a relatively large sample and the extension of a burgeoning contemporary developmental theory of shyness and self-regulation (Brooker et al, 2016; Hassan et al, 2020; Henderson, 2010; Henderson et al, 2015; Henderson & Wilson, 2017; Lahat et al, 2014; Lamm et al, 2014; Poole et al, 2021; Sette et al, 2018; White et al, 2011) to different contexts using a between-subjects design experimentally manipulating contextual familiarity, and the use various indices of inhibitory control and observed social behavior. However, notwithstanding these strengths, the results should be interpreted within their limitations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, an increased theta/beta ratio is believed to exhibit a lower tendency to self-reported attention control 65,66 , therefore our finding is fully consistent with the knowledge regarding the neuropsychological issues characteristic for FASD patients 67 . This is also because the cognitive deficits, in particular those related with executive functions, are the most important part of the FASD clinical picture 68,69 and significantly contribute to the patients' disability 70 .…”
Section: Discussionsupporting
confidence: 89%
“…Shyness is a key risk factor for the onset of internalizing problems (Liu, Calkins, & Bell, 2021; Poole, Hassan, & Schmidt, 2021) and refers to heightened wariness and anxiety when faced with novel people and situations (Rubin, Coplan, & Bowker, 2009). Other risk markers for internalizing problems that share conceptual similarities with shyness include behavioral inhibition, social wariness, and fear (Buss et al, 2013; Fox et al, 2021).…”
Section: Introductionmentioning
confidence: 99%